Listening to seagrass beds comparing soundscapes in Calero, Lilo-an, Cebu, Philippines before and during the onset of the COVID-19 pandemic - Villacarlos, Jan Ira M. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Anthropophony has been identified as one of the stressors in the marine environment, with levels of anthropogenic noise in our oceans, mainly from vessel traffic, steadily increasing in the last centuries. The lockdown implemented in 2020 to prevent transmission of the COVID-19 virus resulted in an economic slowdown, which reduced shipping operations and other anthropogenic activities. This provided an unprecedented opportunity to investigate how large-scale decreases in human activities impact ocean noise levels. In this study, I investigated and characterised the changes in the soundscape pattern before and during the onset of the COVID-19 pandemic in Calero, Lilo-an, Cebu, Philippines by using the available datasets from February to April 2020 and November 2019 and 2021. Long-term spectrograms (LTS) were generated to visualise the acoustic data and the acoustic complexity index (ACI) was computed for all available datasets. Based on the results, there was a general decrease in the anthropogenic noise (low-frequency noise, <1 kHz) in April 2020 when compared to February and March 2020, and in November 2021 when compared to November 2019. Additionally, there is an observable increase in the biological sounds (median sound levels) and a decrease in the computed ACI values in April 2020 but not in November 2021. The soundscape patterns observed in November 2021 were similar to that of November 2019 with the easing of restrictions on human activities. Thus, the pattern observed in April 2020 (i.e., increase in biophony, decrease in ACI and anthropophony) is only transient (i.e., it only lasts when the anthropogenic sound sources were completely absent from the habitat).